Impact of smoking on experimental gingivitis. A clinical, microbiological and immunological prospective study. (3rd March 2016) - Peruzzo, D. C.; Gimenes, J. H.; Taiete, T.; Casarin, R. C. V.; Feres, M.; Sallum, E. A.; Casati, M. Z.; Kantovitz, K. R.; Nociti, F. H.
Abstract : Objective: The present study assessed the effect of smoking on clinical, microbiological and immunological parameters in an experimental gingivitis model. Material and Methods: Twenty‐four healthy dental students were divided into two groups: smokers ( n = 10); and nonsmokers ( n = 14). Stents were used to prevent biofilm removal during brushing. Visible plaque index (VPI) and gingival bleeding index (GBI) were determined 5‐ on day ‐7 (running phase), baseline, 21 d (experimental gingivitis) and 28 d (resolution phase). Supragingival biofilm and gingival crevicular fluid were collected and assayed by checkerboard DNA–DNA hybridization and a multiplex analysis, respectively. Intragroup comparison was performed by Friedman and Dunn's multiple comparison tests, whereas the Mann–Whitney U ‐test was applied for intergroup analyses. Results: Cessation of oral hygiene resulted in a significant increase in VPI, GBI and gingival crevicular fluid volume in both groups, which returned to baseline levels 7 d after oral hygiene was resumed. Smokers presented lower GBI than did nonsmokers ( p < 0.05) at day 21. Smokers had higher total bacterial counts and higher proportions of red‐ and orange complex bacteria, as well as lower proportions of Actinomyces spp., and of purple‐ and yellow‐complex bacteria ( p < 0.05). Furthermore, the levels of key immune‐regulatory cytokines, including interleukin (IL)‐8, IL‐17 and interferon‐γ, were higher in smokers than in nonsmokers ( p < 0.05). Conclusion: Smokers and nonsmokers developed gingival inflammation after supragingival biofilm accumulation, but smokers had less bleeding, higher proportions of periodontal pathogens and distinct host‐response patterns during the course of experimental gingivitis.